Case Report: The Effect of Ajwa Dates on Calcium Levels in Perimenopausal Women - Rahma, Muftihatur; Mappaware, Nasrudin Andi; Diana, Ajar; Nulanda, Mona; Hamsah, M.; Surdam, Zulfiah (Journal La Medihealtico, 2024)
Perimenopause itself is defined as the permanent cessation of menstruation due to loss of ovarian activity confirmed by the onset of amenorrhea for 12 consecutive months in the absence of other pathological or physiological causes, occurring at the age of 42 years until menopause. In perimenopausal women, besides decreasing estrogen levels, there is also a decrease in calcium absorption which causes osteoporosis. Where dates contain iron, magnesium, calcium, phosphorus and potassium, but it also contains phytochemical compounds such as phytosterols and phytoestrogens. Phytoestrogens have the same structure and function as endogenous estrogens that serve to exert a major effect on women on bone remodeling and also control the timing of osteoclast apoptosis. Objective : To determine the relationship between giving ajwa dates to calcium levels in perimenopausal women. Method : Literature review with narrative review design. Results : Based on several journals that have been reviewed, it can be concluded that giving ajwa dates can inhibit the decrease in bone density in elderly women, where the active substances that play a role in this are calcium and phytoestrogens. Conclusion : Giving ajwa dates can inhibit the decrease in bone density in elderly women. Keywords : ajwa date (Phoenix dactylifera L), perimenopause, calcium.